Perencanaan Bisnis pada Aspek Keuangan Swipewash Marketplace untuk Layanan Laundry - Amatullah, Nida; Negoro, Dimas; Kustiawan, Unggul; Abadi, Ferryal (Berdikari: Jurnal Inovasi dan Penerapan Ipteks, 2025)
This research aims to examine and assess the financial planning executed in Swipewash Marketplace, a platform for laundry service, to facilitate efficient financial management and promote sustainable business growth. This research identifies that 74% of respondents consider laundry services as a basic need, with 57.7% are loyal customers and 16.3% are classified as non-regular customers. Furthermore, 20% of respondents need the pick-up and delivery services, although 6% value clarity about washing status. This data illustrates the lifestyle of Tangerang residents who emphasize efficiency and convenience, positioning Swipewash as a substantial opportunity to address these demands. The analysis indicates that 62% of laundry services in Tangerang offer pick-up and delivery services, although 40.92% have difficulties in their management. For about 38% of laundry businesses do not offer pick-up and delivery services. The methodology employed a blend of qualitative and quantitative techniques, involving data collection via management interviews, operational observations, and examination of financial reports and planning documents. The research findings underscore the significance of cash flow management strategies, pragmatic budgeting, and cost control as the cornerstone of effective financial planning. This research encompasses financial estimates, cash flow analysis, initial capital assessment, and investment feasibility review. The findings suggest that the Swipewash Marketplace business model possesses significant economic potential and offers an appealing return on investment. A sensitivity analysis was performed to assess the effect of variations in operating expenses and service prices on business viability. Through meticulous financial planning, Swipewash Marketplace is anticipated to expand and gain the advantages for both laundry service providers and customers